The evaluation of gains and losses related to menopause and the intensity of menopausal symptoms. An analysis within the framework of conservation of resources theory by Stevan E. Hobfoll - Bielawska-Batorowicz, Eleonora; Mikołajczyk, Marzena (Menopause Review/Przegląd Menopauzalny, 2009)
Objective: The study used the assumptions of the conservation of resources (COR) theory by S. Hobfoll to: • find out what kinds of resources were gained or lost during menopausal transition, • to examine the relationship between the evaluation of gains and losses and the intensity of menopausal symptoms as well as the relationship between attitudes towards menopause and the evaluation of gains and losses. Material and methods: Ninety-one women aged 47-55 yrs participated in the study and 43 of them were on hormonal therapy (HT). The Menopausal Representation Questionnaire and Evaluation of Resources questionnaire were administered. Results: Women on HT and those without HT named different gains and losses during the preceding year. Women on HT more often listed gains and losses related to personal life and individual characteristics, while those without HT listed gains related to family situation and losses related to health. High evaluation of losses and low evaluation of gains were correlated with the intensity of menopausal symptoms irrespective of HT. Attitudes towards menopause were also linked to evaluation of gains and losses. High evaluation of gains and low evaluation of losses were correlated with the beliefs that symptoms related to menopause were limited to a short period of time and that women could have control over the menopausal transition. Conclusions: The results indicate the applicability of COR theory for analyses of women’s experiences during the menopausal transition.